2017
DOI: 10.1016/j.jvoice.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory and Inspiratory Cries Detection Using Different Signals' Decomposition Techniques

Abstract: This paper addresses the problem of automatic cry signal segmentation for the purposes of infant cry analysis. The main goal is to automatically detect expiratory and inspiratory phases from recorded cry signals. The approach used in this paper is made up of three stages: signal decomposition, features extraction, and classification. In the first stage, short-time Fourier transform, empirical mode decomposition (EMD), and wavelet packet transform have been considered. In the second stage, various set of featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Based on the results obtained from our previous works (Abou-Abbas et al , 2017; Abou-Abbas et al , 2015c) regarding finding the best IMF combination, we have found that the parameters extracted from the sum of IMF3, IMF4, and IMF5 yielded the best cry segmentation results. Therefore, this combination was employed in this work: IMF345 = IMF3 + IMF4 + IMF5.…”
Section: Theoretical Backgroundmentioning
confidence: 66%
See 2 more Smart Citations
“…Based on the results obtained from our previous works (Abou-Abbas et al , 2017; Abou-Abbas et al , 2015c) regarding finding the best IMF combination, we have found that the parameters extracted from the sum of IMF3, IMF4, and IMF5 yielded the best cry segmentation results. Therefore, this combination was employed in this work: IMF345 = IMF3 + IMF4 + IMF5.…”
Section: Theoretical Backgroundmentioning
confidence: 66%
“…Our database in this work consists of a total of 507 waveforms of cry sounds interspersed by different unwanted acoustic activities. A summary of the database is given in Tables II and III, and it is the same database as used in our previous work (Abou-Abbas et al , 2017) for comparison purposes.…”
Section: Corpus Of Infants' Criesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an automatic cry segmentation system is proposed as a pre-processing step in the infant cry classification task [13]. Other notable studies for infant cry classification include the works reported in [14][15][16][17][18][19][20][21]. The detailed discussion on the topic of infant cry classification is found in [7] and in [22], the first Ph.D. thesis from India in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Flowchart of adopted approach.In the first step, cry signals were processed manually using PRAAT (a freeware program for the analysis and reconstruction of acoustic speech signals)[29]. The automated preprocessing method is currently being investigated by other researchers studying the PICS[30]. Because the recorded sounds include the background noises, speech, sound of medical equipment, and silence, some of these parts may distort the results of the analysis.…”
mentioning
confidence: 99%